Phylogeographical features of Octopus vulgaris and Octopus insularis in the southeastern atlantic based on the analysis of mitochondrial markers - Sales, João Bráullio de Luna (2013)
The genus Octopus occurs in tropical and temperate oceanic waters throughout the world, and currently includes 112 species, although the phylogenetic relationships among the different taxa are still poorly understood. The cosmopolitan Octopus vulgaris is one of the most widely analyzed cephalopods in genetic studies, primarily because of its ample range and the problems associated with the morphological identification of specimens, which indicate the possible existence of a species complex with a worldwide distribution. Two large-bodied octopus species—O. vulgaris and Octopus insularis—are found in the western South Atlantic. The limits of the geographical range of the O. insularis are still unclear. The current study is based on a phylogeographic analysis of the 2 species in the South Atlantic, with the objective of confirming their monophyletic status and the limits of their geographical distribution in this region. The analyses were based on the mitochondrial genes 16S rDNA and Cytochrome Oxidase subunit I (COI). The topologies generated for both genes confirmed the monophyletíc status of the 2 species. In the case of O. vulgaris, it was possible to confirm the monophyletic status of the specimens from this region relative to those of other areas around the world, although 3 distinct haplogroups were clearly differentiated, corresponding to the Americas, Europe and Africa, and Asia. The differentiation among these 3 groups may be determined by the limitations of the dispersal of paralarvae among continents. Further studies are needed to confirm the possible occurrence of distinct groups in the western South Atlantic, as well as the influence of oceanic currents on the phylogeographical distribution of O. vulgaris on the Brazilian coast.